Periapical Lesions Increase Macrophage Infiltration and Inflammatory Signaling in Muscle Tissue of Rats - Pereira, Renato Felipe [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Tessarin, Gestter Willian Lattari [UNESP]; Chiba, Fernando Yamamoto [UNESP]; de Lima Coutinho Mattera, Maria Sara [UNESP]; Scaramele, Natalia Francisco [UNESP]; Tsosura, Thais Verônica Saori [UNESP]; Ervolino, Edilson [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Sumida, Doris Hissako [UNESP] (Elsevier, 2017)
Introduction Our previous studies have shown that periapical lesions (PLs) in rats cause systemic disorders such as increased tumor necrosis factor-α plasma levels, insulin resistance, and impairment in insulin signal transduction in muscle tissue. However, the mechanisms involved in these alterations are not fully understood. Under chronic inflammatory conditions such as obesity, it has been shown that the skeletal muscle is affected by inflammation, and the number of resident macrophages that are associated with impairments of insulin action and sensitivity is increased. This study aimed to investigate the presence of macrophages, activation of inflammatory pathways in muscle tissue, glycemia, and insulinemia of rats with PLs. Methods Sixty Wistar rats were distributed into a control group; a group with 1 PL (1PL), which was induced in the right maxillary first molar; and a group with 4 PLs (4PL), which were induced in the right upper and lower first and second molars. We quantified macrophage content by immunohistochemistry for the F4/80 protein. We evaluated Jun N-terminal kinase and IKKα/β phosphorylation status in the muscle tissue by Western blotting. Serum levels of lipopolysaccharide (LPS) and HSP70 and plasma levels of glucose and insulin were assessed by using commercial kits. Results The 1PL and 4PL groups showed increase in macrophage content, IKKα/β, and Jun N-terminal kinase phosphorylation status, serum LPS and HSP70 levels, and insulin resistance and no changes in glycemia and insulinemia compared with the control group. There was no difference in these parameters between the 1PL and 4PL groups. Conclusions PLs promoted an increase in macrophage infiltration, activation of inflammatory pathways in muscle tissue, and serum concentrations of HSP70 and LPS in rats. The present study improves the knowledge on the impact of oral inflammations on the development of systemic alteration, which can induce insulin resistance.
Keywords: Inflammation; insulin resistance; periapical lesion; systemic disorders